2019
DOI: 10.1017/s0263034619000697
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear propagation of ion acoustic waves in quantum plasma in the presence of an ion beam

Abstract: Nonlinear propagation of ion acoustic waves has been studied in unmagnetized quantum (degenerate) plasma in the presence of an ion beam using the one-dimensional quantum hydrodynamic model. The Korteweg–de Vries (K–dV) equation has been derived by using the reductive perturbation technique. The solution of ion acoustic solitary waves is obtained from the K–dV equation. The theoretical results have been analyzed numerically for different values of plasma parameters and the results are presented graphically. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…[19,20] Moreover, the impact of Bohm potential on the linear and nonlinear characteristics of longitudinal waves has already been extensively studied in numerous works. [35][36][37][38] Since in the present analysis, we want to focus mainly on the signatures of spin polarization and beam on the solitary waves, so for the sake of simplicity the Bohm potential force has not been taken into account in present study (see, i.e., Equation 4). The Poisson equation for longitudinal waves in electron-ion-beam plasma reads as…”
Section: Model Equationsmentioning
confidence: 99%
“…[19,20] Moreover, the impact of Bohm potential on the linear and nonlinear characteristics of longitudinal waves has already been extensively studied in numerous works. [35][36][37][38] Since in the present analysis, we want to focus mainly on the signatures of spin polarization and beam on the solitary waves, so for the sake of simplicity the Bohm potential force has not been taken into account in present study (see, i.e., Equation 4). The Poisson equation for longitudinal waves in electron-ion-beam plasma reads as…”
Section: Model Equationsmentioning
confidence: 99%
“…Solving the system of Eqs. ( 27)- (31) with the aid of Eqs. ( 18)-( 26), we get finally the following nonlinear partial differential equation…”
Section: Derive Zakharov-kuznetsov Equationmentioning
confidence: 99%
“…They assumed that the plasma is to be rotating with angular frequency at an angle 𝜃 to the direction of the magnetic field. Paul et al [31] studied the nonlinear propagation of ion acoustic waves in unmagnetized quantum plasma in the presence of an ion beam using the one-dimensional quantum hydrodynamic model. They have found that the formation and structure of solitary waves are significantly affected by the ion beam .…”
Section: Introductionmentioning
confidence: 99%
“…Solitary waves in a dense plasma with ion beam were studied in ref. [26], and their findings were based on the KdV equation, and it was shown that the existence of ion beams in plasma considerably impacted the formation and structure of solitary waves. In ref.…”
Section: Introductionmentioning
confidence: 99%